Split-VMAT technique to control the expiratory breath-hold time in liver stereotactic body radiation therapy. (August 2017) - Lin, Yen Hwa; Ozawa, Shuichi; Miura, Hideharu; Yogo, Katsunori; Nakashima, Takeo; Miki, Kentaro; Tsuda, Shintaro; Ochi, Yusuke; Kawahara, Daisuke; Kimura, Tomoki; Saito, Akito; Nagata, Yasushi
Highlights: A systematic approach of stereotactic body radiation therapy is proposed. Volumetric modulated radiation therapy at fully expiratory breath-hold is used. Verification methods prior to clinical implementation is demonstrated. High target conformation and low mean dose of healthy liver tissues are observed. Split-VMAT technique is able to control beam-on time. Abstract: Purpose: In this study, we demonstrate the feasibility of using split-arcs in volumetric modulated arc therapy (VMAT), tailored for expiratory breath-hold in stereotactic body radiation therapy (SBRT) for liver tumors. We compare it with three-dimensional conformal radiation therapy (3D-CRT) and continuous-VMAT, for ten randomly selected hepatocellular carcinoma cases. Methods: Four coplanar and four non-coplanar beams were used for the 3D-CRT plans. A pair of partial arcs, chosen using a back-and-forth rotating motion, were used for the continuous-VMAT plans. Split-VMAT plans were created using the same arc range as the continuous-VMAT plans, but were split into smaller arcs (<90°), to simulate an expiratory breath hold of <15 s. The dose distribution, treatment delivery efficiency, and patient specific quality assurance of the split-VMAT, were verified to ensure that the outcomes were equal, or better than, those for 3D-CRT and continuous-VMAT. The prescription was 48 Gy/4 fractions, to 95% of the PTV, using 10 MV FFF X-ray beams. Results: The mean dose of the liver-GTV was lower in the split-VMAT compared with that of 3D-CRT. Split-VMAT was more conformal compared with 3D-CRT. The total treatment time for split-VMAT was shorter than that of 3D-CRT. Similar dosimetric indices were observed for split-VMAT and continuous-VMAT. All VMAT plans passed the gamma acceptance test. Conclusions: Split-VMAT designed to accommodate an expiratory breath-hold period of 15 s is a feasible and efficient use of liver SBRT, because it does not compromise the quality of the plan, when compared with 3D-CRT or continuous-VMAT.